Steroids Static Postural Balance Changes After Exercise Intervention Correlate with Steroidome in Elderly Female - Zuzanna Kornatovská; Martin Hill; Dobroslava Jandová; Milada Krejčí; Anna Zwierzchowska (Metabolites)
Background: Aging is associated with the development of various disorders, including postural imbalance, which increases the risk of falls and related health complications. This study examines changes in static postural balance after a 4-week intervention involving appropriate exercise and an optimized daily regimen. Additionally, it explores the relationship between these changes and the steroidome. Methods: The study was conducted on a clinically homogeneous group of 41 females around their sixth decade, diagnosed with anxiety-depressive syndrome and treated with selective serotonin reuptake inhibitors (SSRIs). Postural balance was assessed using the dual-scales method (DLLL-DSM), which estimates postural imbalance by evaluating differences in the lower limb load in the standing position. Correlations between initial DLLL-DSM values, age, BMI, and the baseline levels of nine serum steroids, as well as post-intervention changes in five steroids, were analyzed using multivariate regression (OPLS model). Results: A significant reduction in lower limb load differences (-ΔDLLL-DSM), indicating improved postural balance, was observed. The -ΔDLLL-DSM strongly correlated with initial DLLL-DSM values, age, BMI, initial levels of nine serum steroids, and post-intervention changes in five steroids (R = 0.892, p < 0.001). Furthermore, initial DLLL-DSM values negatively correlated with adrenal androgen androstenediol sulfate and various sulfated 5α/β-reduced androgen metabolites (R = 0.323, p < 0.05), suggesting that the activity of steroid sulfotransferase (SULT2A1) and C17-hydroxylase-C17,20-lyase (CYP17A1) at the lyase step is negatively associated with postural imbalance in elderly females. Conclusions: The findings suggest that even severe postural imbalance can be effectively and relatively rapidly improved through an appropriate exercise-based intervention and an optimized daily regimen, provided that initial adrenal activity is not significantly impaired. Additionally, the identified associations between steroid levels and postural balance provide new insights into the hormonal mechanisms regulating balance control in older individuals.